Implementing and certifying ISO 14001 in Portugal: motives, difficulties and benefits after ISO 9001 certification - Santos, Gilberto (2015)
The purpose of this study is to characterise the environmental management systems (EMS) certification process (International Organization for Standardization (ISO) 14001) in Portuguese small and medium enterprises (SMEs) following quality management system (QMS) certification (ISO 9001). The study is based on a sample from Portuguese SMEs which characterise the local reality in terms of companies certified in accordance with ISO 14001 after ISO 9001 certification. Some Portuguese SMEs have the EMS implemented but not certified, mainly given the lack of investment support and because it is considered merely a form of marketing. As such, they do not feel motivated to certificate an EMS in the company since they consider that it is a form of advertising and not a way to protect the environment. Nonetheless, it is already evident form other Portuguese SMEs that gained EMS certification that gains supersede marketing benefits and allow for evermore enduring benefits such as prevention of environmental risks, environment protection, improved company image, compliance with legislation and efficient use of natural resources. This paper also presented the main difficulties in achieving an EMS certification, including high certification costs, human resources, motivation issues and difficulties in changing the company’s culture.